2018
DOI: 10.3389/fpsyg.2018.01477
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness as a Moderator in the Relation Between Income and Psychological Well-Being

Abstract: The relation between income and life satisfaction has been found to be weak, albeit positive (r = 0.10–0.20). This study introduced psychological well-being (PWB) as a dependent variable predicted by income in addition to life satisfaction. Furthermore, individual differences might determine the strength of this relation, that is, act as moderators. Thus, this study introduced mindfulness as one such possible moderator. Participants (N = 800, 50% women, aged 20–59 years) completed an Internet questionnaire. Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 38 publications
1
12
0
1
Order By: Relevance
“…For example, in the existing literature, there are some differences in the internal correlations among subcomponents of the FFMQ between the results from Western participants and Eastern participants. Specifically, observing has been documented as negatively correlating with non-judging and acting with awareness in Eastern cultures (25,(36)(37)(38)(39)(40)(41), and our results are consistent with these results. In contrast, in Western cultures (14)(15)(16)22), almost all components of the FFMQ positively correlated with each other.…”
Section: Discussionsupporting
confidence: 91%
“…For example, in the existing literature, there are some differences in the internal correlations among subcomponents of the FFMQ between the results from Western participants and Eastern participants. Specifically, observing has been documented as negatively correlating with non-judging and acting with awareness in Eastern cultures (25,(36)(37)(38)(39)(40)(41), and our results are consistent with these results. In contrast, in Western cultures (14)(15)(16)22), almost all components of the FFMQ positively correlated with each other.…”
Section: Discussionsupporting
confidence: 91%
“…For balanced meals, studies in the United States have identified positive associations with community gardening [7]. As a hypothesis, it could be inferred that there were conflicts with economic status, because the relationship between these items and economic status has been reported in Japan [17,42,43,44,45]. People who have a home garden may be economically better off.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the positive relationship between perceived social support and well-being is promoted by dispositional mindfulness (Stallman et al, 2018). Furthermore, dispositional mindfulness can be seen as a moderator for the relationship between income and well-being (Sugiura and Sugiura, 2018). Dispositional mindfulness acts as a moderator for the relationship between social factors and well-being because awareness and observation without making judgments increases the enjoyment of experiences and can highlight the joy in every aspect of an individual's daily experience (Sugiura and Sugiura, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, dispositional mindfulness can be seen as a moderator for the relationship between income and well-being (Sugiura and Sugiura, 2018). Dispositional mindfulness acts as a moderator for the relationship between social factors and well-being because awareness and observation without making judgments increases the enjoyment of experiences and can highlight the joy in every aspect of an individual's daily experience (Sugiura and Sugiura, 2018). Therefore, even if an individual's living environment is not satisfactory, if their dispositional mindfulness is high, it is possible to find pleasure in life, which may lead to the individual taking action toward social contact.…”
Section: Introductionmentioning
confidence: 99%